ANALYSIS OF THE INFLUENCE OF HUMAN RESOURCES COMPETENCE, MOTIVATION, WORK ENVIRONMENT AND THE ROLE OF LEADERSHIP ON THE PERFORMANCE OF ASSET STEWARD IN THE ORGANIZATION OF REGIONAL DEVICES SERDANG BEDAGAI REGENCY - Situmorang, Resman Budiman (International Journal of Public Budgeting, Accounting and Finance, 2019)
The research objective is to test and analyse The Influence of Human Resources Competence, Motivation, Work Environment and the Role of Leadership on the Performance Of asset Steward in The Organization of Regional Devices (47 OPD) Serdang Bedagai Regency. The research is causal associative. The whole population is taken as the research samples (47 Asset Steward  in The Organization Of Regional Devices). Hypothesis testing uses multiple linear regression with coefficient of determination, F-test and t-test. The results of this research indicate that the partial and simultaneous variables of human resources competence, motivation, work environment and the role of leadership have a significant positive effect on the performance of asset steward in The Organization of Regional Devices Serdang Bedagai Regency. The value of R Square obtained is 0.866 with the explanation that 86,6% variable of performance of asset steward is explained by human resources competence, motivation, work environment and role of leadership and 13,4% is explained by other variable outside variable which used in this research.